Run (HarperLuxe, Recorded Books, HarperCollins, HarperAudio, HarperCollins Publishers, Harper Audio, 2009)
Tip and Teddy are becoming men under the very eyes of their adoptive father, Bernard Doyle. A student at Harvard, Tip is happiest in a lab, whilst Teddy thinks he has found his calling in the Church, and both are increasingly strained by their father's protective plans for them. But when they are involved in an accident on an icy road, the Doyles are forced to confront certain truths about their lives, how the death of Doyle's wife Bernadette has affected the family, and an anonymous figure who is always watching.

Maine: a novel (Thorndike Press large print core, ,, 2012)
Three generations of women converge on the family beach house in this wickedly funny, emotionally resonant story of love and dysfunction.

Moonglow: a novel (Harper Audio, HarperCollins Publishers, HarperCollins, HarperLuxe, an imprint of HarperCollins Publishers, HarperAudio, Harper, an imprint of HarperCollinsPublishers, Harper Audio, HarperCollins Publishers, 2016)
A man bears witness to his grandfather's deathbed confessions, which reveal his family's long-buried history and his involvement in a mail-order novelty company, World War II, and the space program.

Shanghai girls: a novel (Shanghai Girls, ,, 2009)
In the mid 1930's two well-educated sisters from Shanghai go to Los Angeles to become brides of the "Gold Mountain men" when their family is on the verge of bankruptcy. When they get there they are detained, interrogated, and humiliated for months. When one of the sisters becomes pregnant they vow that no one will ever know.

The tiger's wife: a novel (Reader's circle), ,, 2011)
NEW YORK TIMES BESTSELLER • NATIONAL BOOK AWARD FINALIST • The instant classic debut novel from the author of Inland and The Morningside, hailed as “a thrilling beginning to what will certainly be a great literary career” (Elle)   “Spectacular . . . [Téa Obreht] spins a tale of such marvel and magic in a literary voice so enchanting that the mesmerized reader wants her never to stop.”—Entertainment Weekly   “Not since Zadie Smith has a young writer arrived with such power and grace.”—Time ONE OF THE TEN BEST BOOKS OF THE YEAR: Michiko Kakutani, The New York Times; Entertainment Weekly; The Christian Science Monitor; The Kansas City Star; Library Journal In a Balkan country mending from war, Natalia, a young doctor, is compelled to unravel the mysterious circumstances surrounding her beloved grandfather’s recent death. Searching for clues, she turns to his worn copy of The Jungle Book and the stories he told her of his encounters over the years with “the deathless man.” But most extraordinary of all is the story her grandfather never told her—the legend of the tiger’s wife.   Weaving a brilliant latticework of family legend, loss, and love, Téa Obreht, hailed by Colum McCann as “the most thrilling literary discovery in years,” has spun a timeless novel that will establish her as one of the most vibrant, original authors of her generation. ONE OF THE BEST BOOKS OF THE YEAR: The Wall Street Journal, O: The Oprah Magazine, The Economist, Vogue, Slate, Chicago Tribune, The Seattle Times, Dayton Daily News, Publishers Weekly, Alan Cheuse, NPR’s All Things Considered

A reliable wife (Recorded Books, Inc., Algonquin Books of Chapel Hill, Recorded Books, Playaway Digital Audio, Algonquin Books, Thorndike Press, 2009)
Rural Wisconsin, 1907. In the bitter cold, wealthy businessman Ralph Truitt stands alone on a train platform waiting for the woman who has answered his advertisement for "a reliable wife." But when Catherine Land steps off the train from Chicago, she's not the "simple, honest woman" Ralph is expecting. She is both complex and devious, but her plan is simple: she will win this man's devotion, then slowly poison him and leave Wisconsin a wealthy widow. What she has not counted on is that Truitt has a plan of his own for his new wife. (Bestseller)

The particular sadness of lemon cake: a novel (Thorndike Press large print reviewers choice, ,, 2011)
"On the eve of her ninth birthday, unassuming Rose Edelstein, a girl at the periphery of schoolyard games and her distracted parents' attentions, bites into her mother's homemade lemon-chocolate cake and discovers she has a gift: she can taste her mother's emotions in the cake. But her gift is no blessing, for her mother - her cheerful, good-with-crafts, can-do mother - tastes of despair and desperation. Suddenly, and for the rest of her life, food becomes a peril and a threat to Rose."--Back cover.

Beautiful day: a novel (AudioGO, Little Brown & Company, Back Bay Books, Little, Brown, and Company, Little, Brown, & Company, Hachette Audio, Little, Brown and Company, 2014)
The Carmichaels and the Grahams have gathered on Nantucket for a wedding. Plans are being made according to the wishes of the bride's late mother, who left behind The Notebook: specific instructions for every detail of her youngest daughter's future nuptials. Everything should be falling into place for the beautiful event--but in reality, things are far from perfect. While the couple-to-be are quite happy, their loved ones find their own lives crumbling. In the days leading up to the wedding, love will be questioned, scandals will arise, and hearts will be broken and healed.

Take me on (Pushing the limits, 4, 1, 2017)
Abandoning kickboxing after a tragedy in the ring, champion fighter Haley is forced to train an attractive mixed martial arts student who secretly fights on Haley's behalf to redeem his troubled past.

The castaways: a novel (Nantucket, ,, 2009)
Greg and Tess MacAvoy are one of four prominent Nantucket couples who count each other as best friends. As pillars of their close-knit community, the MacAvoys, Kapenashes, Drakes, and Wheelers are important to their friends and neighbors, and especially to each other. But just before the beginning of another idyllic summer, Greg and Tess are killed when their boat capsizes during an anniversary sail. As the warm weather approaches and the island mourns their loss, nothing can prepare the MacAvoy's closest friends for what will be revealed.--From publisher description.

Sarah's key (St Martins Press/Macmillan, St. Martin's Press, BBC Audiobooks America, St. Martin's Griffin, Macmillan Audio, Thorndike Press, 2009)
Paris, July 1942: Sarah, a ten year-old girl, is brutally arrested with her family by the French police in the Vel d'Hiv' roundup, but not before she locks her younger brother in a cupboard in the family's apartment, thinking that she will be back within a few hours. Paris, May 2002: On Vel d'Hiv's 60th anniversary, journalist Julia Jarmond is asked to write an article about this black day in France's past. Through her contemporary investigation, she stumbles onto a trail of long-hidden family secrets that connect her to Sarah. Julia finds herself compelled to retrace the girl's ordeal, from that terrible term in the Vel d'Hiv', to the camps, and beyond. As she probes into Sarah's past, she begins to question her own place in France, and to reevaluate her marriage and her life.

Family pictures (Wheeler Publishing, St. Martin's Press, St. Martin's Griffin, Macmillan Audio, 2014)
As dark truths from the past reveal themselves, two middle-aged women must learn to forgive -- for the sake of their children and themselves.

Eyes wide open (HarperLuxe, AudioGO, William Morrow, Blackstone Audio, HarperCollins, HarperAudio, HarperCollins Publishers, 2011)
"Gross is a top-notch thriller writer." —Chicago Sun-Times "Andrew Gross knows how to make your skin crawl. Eyes Wide Open should be read with the door shut and the lights on; a truly terrifying descent into evil." —Nelson DeMille New York Times bestselling author Andrew Gross solidifies his position as one of today's very best suspense authors with Eyes Wide Open. Joining his previous bestsellers The Blue Zone, The Dark Tide, Don't Look Twice, and Reckless, Eyes Wide Open is another brilliant example of the contemporary thriller done absolutely right. In this relentlessly exciting page-turner, a man must investigate a shattering personal tragedy that is somehow connected with a charismatic cult leader from the '60s. James Patterson, Harlan Coben, David Baldacci, John Grisham, Jonathan Kellerman, Jeffery Deaver, Lisa Gardner, Nelson DeMille, Tess Gerritsen—Andrew Gross stands tall in their elite company.

Wreck the halls: a novel (Harper Large Print, an imprint of HarperCollinsPublishers, Blackstone Audio, Avon, an imprint of HarperCollins Publishers, HarperCollins, HarperAudio, 2023)
Stepping out of her comfort zone with her former best friend Beat Dawkins to convince their mothers to perform one last concert on Christmas Eve, Melody Gallard, the daughter of music royalty, discovers a decades-old scandal threatens to wreck everything--the reunion, their relationships with their mothers and their newfound love.

Clap when you land (HarperCollins, Quill Tree Books, HarperTeen, an imprint of HarperCollinsPublishers, HarperCollins Publishers, 2020)
Two sisters mourn their father's death after his plane crashes on a flight to the Dominican Republic.

The lost vintage: a novel (HarperLuxe, an imprint of HarperCollinsPublishers, HarperCollins, HarperAudio, William Morrow, an imprint of HarperCollinsPublishers, Harper Audio, HarperCollins Publishers, 2018)
"Sweetbitter meets The Nightingale in this page-turner about a woman who returns to her family's ancestral vineyard in Burgundy to study for her Master of Wine test, and uncovers a lost diary, a forgotten relative, and a secret her family has been keeping since WWII"--

Eight hundred grapes: a novel (S&S/ Marysue Rucci Books, Simon & Schuster Audio, Center Point Large Print, Simon & Schuster, 2015)
"A story, set in the Sonoma wine valley, about the messy realities of family, the strength (and weaknesses) of romantic love, and the importance of finding a place to call home"--

Truth or die (Hachette Audio, Blackstone Audio, Inc, Little, Brown and Company, 2015)
When his journalist girlfriend's latest scoop leads to a violent confrontation, attorney Trevor Mann discovers a shocking secret that governments and terrorist organizations would do anything to possess. "After a serious professional stumble, attorney Trevor Mann may have finally hit his stride. He's found happiness with his girlfriend Claire Parker, a beautiful, ambitious journalist always on the hunt for a scoop. But when Claire's newest story leads to a violent confrontation, Trevor's newly peaceful life is shattered as he tries to find out why. Chasing Claire's leads, Trevor unearths evidence of a shocking secret that-if it actually exists-every government and terrorist organization around the world would do anything to possess. Suddenly it's up to Trevor, along with a teenage genius who gives new meaning to the phrase "too smart for his own good," to make sure that secret doesn't fall into the wrong hands. But Trevor is about to discover that good and evil can look a lot alike, and nothing is ever black and white: not even the truth" --

The nix (Thorndike Press large print Bill's bookshelf, ,, 2017)
It’s 2011, and Samuel Andresen-Anderson hasn’t seen his mother, Faye, in decades—not since she abandoned the family when he was a boy. Now she’s reappeared, having committed an absurd crime that electrifies the nightly news and inflames a politically divided country. The media paints Faye as a radical hippie with a sordid past, but as far as Samuel knows, his mother was an ordinary girl who married her high-school sweetheart. Which version of his mother is true? Two facts are certain: she’s facing some serious charges, and she needs Samuel’s help. To save her, Samuel will have to embark on his own journey, uncovering long-buried secrets about the woman he thought he knew, secrets that stretch across generations and have their origin all the way back in Norway, home of the mysterious Nix. As he does so, Samuel will confront not only Faye’s losses but also his own lost love, and will relearn everything he thought he knew about his mother, and himself.
The packer attacker , Ghosts of the old country , Enemy, obstacle, puzzle, trap , The house spirit , A body for each of us , Invasive species , Circle , Search and seizure , Revolution , Deleveraging.

Lisey's story: a novel (Thorndike press large print basic, ,, 2006)
After losing her husband of twenty-five years, Lisey looks back at the sometimes frightening intimacy that marked their marriage, her husband's successes as a novelist, and his secretive nature that established her supernatural belief systems.